Manajemen Jam’iyah Batak Muslim Indonesia (JBMI) Dalam Meningkatkan Kualitas Da’i di Tapanuli Utara - Akbar Sholeh Sihombing, Hasnun Jauhari Ritonga; Ritonga, Hasnun Jauhari (LP2M IAI Miftahul Ulum Pamekasan, 2025)
This study aims to determine the Management of Jam'iyah Batak Muslim Indonesia (JBMI) in Improving the Quality of Da'i in North Tapanuli. Jam'iyah Batak Muslim Indonesia (JBMI) is part of an organization in the field of da'wah and also as a forum or place of bersilaturrahmi, which aims to gather the Indonesian Muslim Batak community in jam'iyah to build devoted humans in ukhuwah and kinship. This research uses a qualitative approach with a field study design (field research). Data were collected through in-depth interviews with JBMI administrators at the regional level (DPW), the council of scholars, and the advisory board, as well as observation and document study. Data analysis techniques used the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the application of four management functions (POAC) in the management of JBMI's da'wah is quite effective. Planning is done thematically and periodically, organizing is supported by a systematic structure from central to branch level, and program implementation includes activities such as majelis taklim, seminars, Batak Sufi pilgrimage, and publishing books of local ulama figures. Supervision is applied through regular evaluation of da'wah activities. Indicators of success can be seen from the increase in community participation, the formation of young da'i cadres, and the maintenance of Islamic identity in harmony with local culture.